Austrodiplostomum compactum Szidat & Nani (Digenea: Diplostomidae) in final and second intermediate hosts from upper São Francisco river in the State of Minas Gerais, Brazil - Monteiro, Cassandra Moraes; Martins, Amanda Nascimento; Albuquerque, Márcia Cavalcanti; Clapp, Michelle Daniele dos Santos; Duarte, Rayane; Sabas, Cláudia da Silveira de São; Sato, Marilia de Carvalho Brasil (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Monteiro C.M., Martins A. N., Albuquerque M.C., dos Santos-Clapp M.D., Duarte R., de São Sabas C. da S. & Brasil-Sato M. de C. Austrodiplostomum compactum Szidat & Nani (Digenea: Diplostomidae) in final and second intermediate hosts from upper São Francisco river in the State of Minas Gerais, Brazil [Austrodiplostomum compactum Szidat & Nani (Digenea, Diplostomidae) nos hospedeiros definitivo e segundo intermediário do alto rio São Francisco, Estado de Minas Gerais, Brasil] Revista Brasileira de Medicina Veterinária, 38(supl. 3): 186-193, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Campus Seropédica, RJ 23897-970, Brasil. E-mail: cassimonteiro@hotmail.com Austrodiplostomum compactum Szidat & Nani, 1954, like others digenetics, have fishes as second intermediate host and piscivorous birds as definitive host. Three neotropic cormorants, Phalacrocorax brasilianus (Gmelin, 1789), from the upper São Francisco River were infected with adults of A. compactum; twenty species of fish, from the São Francisco river, were infected with Austrodiplostomum sp. metacercariae. The parasitic indices were higher in the Perciform and some species of Siluriform than in the majority species of Characiform fishes. Fifteen species of fishes are new record of second intermediate fish hosts in addition to 37 species knew in Brazil. This work contributing with the studies of the helminths and their associated fauna from São Francisco river basin, State of Minas Gerais, Brazil.